2001
DOI: 10.1016/s0020-7292(01)00406-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between age, histological type, and size of ovarian tumors

Abstract: The distribution of tumor histological type (tumor-like lesions, benign, LMP and malignant) was correlated against patient age and lesion diameter, with tumors in older patients or larger tumors more likely to be malignant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 7 publications
3
23
3
Order By: Relevance
“…Only 0.77% of borderline tumor was observed in the present study, which was lower than the studies by Gupta et al, 11 and Okugawa et al, 10 both studies had observed 4% of borderline ovarian tumors.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Only 0.77% of borderline tumor was observed in the present study, which was lower than the studies by Gupta et al, 11 and Okugawa et al, 10 both studies had observed 4% of borderline ovarian tumors.…”
Section: Discussioncontrasting
confidence: 87%
“…There was similar observation by Bhattacharya et al 9 and Okugawa et al, 10 92.59% of ovarian neoplasms while 7.41% of nonneoplastic ovarian lesions; and 72% of ovarian neoplasms and 28% of non-neoplastic lesions respectively. In contrast, Gupta et al 11 observed 41.20% of ovarian neoplasms and 58.80% of non-neoplastic ovarian lesions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Only 1.6% of borderline tumor was observed in the present study, which was lower than the studies conducted by Gupta et al , [7] and Okugawa et al , [8] where both the studies had observed 4% of the borderline ovarian tumors.…”
Section: Discussioncontrasting
confidence: 88%
“…This result is comparable with the study carried out at Tribhuvan University Teaching Hospital, Nepal, [16] in which germ cell tumors were the second common tumors (42.2%); and is also comparable with different series of studies . [14,15,6,7,8] Bhattacharya et al, [9] and Khan et al , [15] noticed benign neoplasms occurring mostly in between 21 and 40 years of age. The present study observed benign neoplasms in the age group from 21 and above 60 years of age.…”
Section: Discussionmentioning
confidence: 99%